A Simple and Efficient Procedure for Rh(I)‐ and Ir(I)‐complex Catalyzed Para‐hydrogenation of Alkynes and Alkenes in Aqueous Media Resulting in Strong PHIP Effects. Issue 13 (3rd June 2019) - Papp, Gábor; Horváth, Henrietta; Joó, Ferenc
Abstract: Catalytic hydrogenations with para ‐H2 may lead to strong para ‐hydrogen induced polarization (PHIP) and the hyperpolarized probe molecules may enable the application of the Magnetic Resonance Imaging (MRI) diagnostic modality for metabolism imaging. The use of water as a solvent for para ‐hydrogenation reactions is very challenging due to the fast exchange between the catalytically active metal hydrides and the water protons and also because of the low hydrogen solubility in water. Here we report that several water‐soluble Rh(I)‐ and Ir(I)‐complexes with N‐heterocyclic carbene (NHC) and/or tertiary phosphine ligands efficiently catalyze the synthesis of hyperpolarized compounds by para ‐hydrogenation in aqueous media. Abstract : hyperpolarized remix : Rh(I)‐ and Ir(I)‐ mixed ligand sulfonated phosphine/N‐heterocyclic carbene complexes, as well as cis, mer ‐[IrH2 Cl( m tppms)3 ], are reported as efficient catalysts for para ‐hydrogenation of unsaturated substrates in aqueous media. A simple procedure is reported for obtaining hyperpolarized probe compounds which may be useful in MR metabolism imaging.